Enhanced production of biosynthesized lycopene via heterogenous MVA pathway based on chromosomal multiple position integration strategy plus plasmid systems in Escherichia coli. (February 2018) - Wei, Yanlong; Mohsin, Ali; Hong, Qi; Guo, Meijin; Fang, Hongqing
Highlights: Construction of a low copy heterogenous mevalonate pathway E. coli . Utilization of chromosomal multiple position integration strategy. Over 2-fold higher maximum average productivity of lycopene than previous reports. The lycopene production was 224 mg/L after the optimization of induction time. The Performance Parameter development for process evaluation. Abstract: The multiple plasmid system, mostly relied, for heterogeneous gene expression, results in genetic instability and low mean productivity. To address this, an integration method was employed for investigating expression of heterogenous pathway in E. coli cells; where mevalonate upper pathway was found efficiently expressed. Subsequently, to improve lycopene production, chromosomal multiple position integration strategy was used to strengthen mevalonate upper pathway. Meanwhile, the plasmid system was employed for mevalonate lower pathway and lycopene pathway expression to finally generate the mutant D711 strain. Comparatively, highest level of 68.5 mg/L lycopene was produced by D711 outperforming its maximum average productivity of 2.85 mg/L/h with over 2-folds enhancement. In addition, lycopene level was almost 224 mg/L after optimization of induction time, which was 3.3-fold higher than standard control condition. Finally, expression Performance Parameter was developed for scoring mutants and evaluating these two strategies, indicating chromosomal multiple position integration strategy as more efficient approach.